Ciudadanía y medio ambiente en las Islas Baleares: el ecobarómetro como instrumento de análisis - Sureda, Jaume; Gili, Margalida; Comas, Rubén; Tudela, Luis; Duce, Este (M+A. Revista Electrónica de Medioambiente, 2009)
The study of the social perception of the environment has turned into an important instrument not just to know the social implication in the environmental themes, but also to orientate and to reorientate the policies. With this motive, this article tries to expose the perception of the Majorcan citizenship with regard to a theme of the maximum importance as the environment, using the Ecobarometer as instrument of analysis.
Keywords: Ecobarometer; Instrument of analysis